Slavistična prepletanja 3 (University of Maribor Press, 2022)
Slavic Intertwining 3.The scientific monograph Slavic Intertwining 3 includes fifteen linguistic contributions that relate to the developmental characteristics of individual Slavic languages and include a comparative aspect of research. The monograph opens with a set of articles that bring current methodological and theoretical approaches in the field of diachrony of Slavic languages to light and shake up existing linguistic theories and terminological use. The second set covers etymological research of Slavic lexica, touches on the standardization of Slavic lexica and lexicographic perspectives. The monograph is rounded off by contributions from the field of Slovene word formation and the development of Slovene lexica. Methodological approaches in Slavic studies, Slavic lexica in different contacts and Slovene lexica are just some of the research challenges of Slavic linguistic research, which is current in terms of both research topics and methodologies